Germination and seed vigor of Phaseolus vulgaris submitted to treatments whit aluminum sulfate - Aleixo da Silva, Josimar; Muniz de Lima, Paula Aparecida; Oliveira Baptista, Julcinara; Carlos Lopes, José; Rocha de Freitas, Allan; Alexandre, Rodrigo Sobreira; de Mello, Tamyris; de Oliveira Lopes, Simone (Emirates Journal of Food and Agriculture, 2023)
The varieties creole are traditionally grown plant, adapted in places where the crops are developed and present in seeds banks of many famers. Thus the objective of this study was to investigate the performance of the germination process and possible toxic effects. Were used seeds of creole cultivars of beans (Phaseolus vulgaris L.), using different concentrations of aluminum. We used a randomized completely design with four repetitions of 25 seeds and the treatments were distributed in 4 x 5 factorial scheme, consisting of four bean cultivars (Carioca, Butter, Black, Red) and five concentrations (0.0, 2.5, 5.0, 7.5, and 10.0 mg L-1) of aluminum sulfate. The characteristics analyzed were percentage of germination, percentage of abnormal seedlings, germination speed index, root length, length of the base of the seedling to the hypocotyl, hypocotyl length of seedlings to the epicotyl, root dry mass and shoot dry mass. The variables germination percentage and germination speed index were not affected by the toxic effect of aluminum. The variables percentage of abnormal seedlings, root length and shoot showed a significant reduction with the increase in aluminum sulfate concentrations, thus showing a greater correlation between them. Keywords: Aluminum; Fabaceae; Physiological quality; Toxicity